Gly126Arg substitution causes anomalous behaviour of α-skeletal and β-smooth tropomyosins during the ATPase cycle. - Rysev, N; Nevzorov, I; Avrova, S; Karpicheva, O; Redwood, C; Levitsky, D; Borovikov, Y (2014)
To investigate how TM stabilization induced by the Gly126Arg mutation in skeletal α-TM or in smooth muscle β-TM affects the flexibility of TMs and their position on troponin-free thin filaments, we labelled the recombinant wild type and mutant TMs with 5-IAF and F-actin with FITC-phalloidin, incorporated them into ghost muscle fibres and studied polarized fluorescence at different stages of the ATPase cycle. It has been shown that in the myosin- and troponin-free filaments the Gly126Arg mutation causes a shift of TM strands towards the outer domain of actin, reduces the number of switched on actin monomers and decreases the rigidity of the C-terminus of α-TM and increases the rigidity of the N-terminus of β-TMs. The binding of myosin subfragment-1 to the filaments shifted the wild type TMs towards the inner domain of actin, decreased the flexibility of both terminal parts of TMs, and increased the number of switched on actin monomers. Multistep alterations in the position of α- and β-TMs and actin monomers in the filaments and in the flexibility of TMs and F-actin during the ATPase cycle were observed. The Gly126Arg mutation uncouples a correlation between the position of TM and the number of the switched on actin monomers in the filaments.